2021
DOI: 10.1002/etc.5135
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Reproductive Toxicity Thresholds for Northern Bobwhite Quail (Colinus virginianus) Exposed to Perfluorohexanoic Acid (PFHxA) and a Mixture of Perfluorooctane Sulfonic Acid (PFOS) and PFHxA

Abstract: Terrestrial toxicology data are limited for comprehensive ecotoxicological risk assessment of ecosystems contaminated by per‐ and polyfluoroalkyl substances (PFAS) partly because of their existence as mixtures in the environment. This complicates logistical dose–response modeling and establishment of a threshold value characterizing the chronic toxicity of PFAS to ecological receptors. We examined reproduction, growth, and survival endpoints using a combination of hypothesis testing and logistical dose–respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(51 citation statements)
references
References 57 publications
2
47
2
Order By: Relevance
“…Collectively, these outcomes demonstrate that PFOS accumulates differently in female versus male northern bobwhite quail liver tissues when mixed with either PFHxS or PFHxA, and indicate that PFOS accumulation due to chronic oral exposure partially depends on the presence of other PFAS (Dennis, Subbiah, et al, 2021; present study). These observations indicate that PFAS mixtures play an important role in chronic avian PFAS toxicity (Dennis et al, 2020; Dennis, Hossain, et al, 2021; Dennis, Subbiah, et al, 2021). As a result, we caution that PFAS ERAs completed prior to these pivotal studies may underestimate potential health risk to avian or other terrestrial receptors (Conder et al, 2020; Divine et al, 2020; Gobas et al, 2020; Larson et al, 2018; Zodrow et al, 2021), and we encourage adoption of these new PFAS LOAEL CTVs in future PFAS ERAs.…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…Collectively, these outcomes demonstrate that PFOS accumulates differently in female versus male northern bobwhite quail liver tissues when mixed with either PFHxS or PFHxA, and indicate that PFOS accumulation due to chronic oral exposure partially depends on the presence of other PFAS (Dennis, Subbiah, et al, 2021; present study). These observations indicate that PFAS mixtures play an important role in chronic avian PFAS toxicity (Dennis et al, 2020; Dennis, Hossain, et al, 2021; Dennis, Subbiah, et al, 2021). As a result, we caution that PFAS ERAs completed prior to these pivotal studies may underestimate potential health risk to avian or other terrestrial receptors (Conder et al, 2020; Divine et al, 2020; Gobas et al, 2020; Larson et al, 2018; Zodrow et al, 2021), and we encourage adoption of these new PFAS LOAEL CTVs in future PFAS ERAs.…”
Section: Resultsmentioning
confidence: 95%
“…This range brackets residues (corresponding to chronic oral toxicity) quantified from the liver of adult and/or juvenile northern bobwhite quail specimens (less than detection limit–133.8 ng/g wet wt; see: Dennis, Subbiah, et al, 2021, repository data) exposed to PFOS and PFHxS at concentrations and mixture ratios typically found in the environment (Anderson et al, 2016; Dennis et al, 2020; East et al, 2020; Filipovic et al, 2015). The present study examined and reported the residues from the livers of adult and juvenile northern bobwhite quail specimens chronically exposed to either PFHxA alone or a binary mixture containing PFOS (Dennis, Hossain, et al, 2021) for a better understanding of the chronic oral toxicity of PFAS to avian receptors.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations